2020
DOI: 10.3390/nano10061128
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ferromagnetism in InGaN Nanostructures Induced by Cr+ ion Implantation

Abstract: This paper presents the magnetic properties of chrome ion (Cr+) implanted InxGa1−xN (x = 0.1, 0.3, 0.5 and 1.0) nanostructures grown by molecular beam epitaxy (MBE). The Cr+ implantation was conducted at 110 keV with three doses, namely 2.6 × 1015, 5.3 × 1015, and 1.3 × 1016 ions/cm2. The as-grown nanostructures exhibited diamagnetism before and after ion implantation without annealing. However, after annealing, the nanostructures exhibited ferromagnetism at room temperature. The saturation magnetization (Ms) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The InGaN films on LT-GaN exhibit emissions corresponding to the near-band transitions (NBE) of GaN located at approximately 3.4 eV, as observed in Figure a . Additionally, a higher-intensity emission between 3.1 and 2.8 eV can be observed and attributed to InGaN NBE because of the shift toward a lower energy according to the indium composition . The band and shoulder observed at 2.62 and 2.26 eV, respectively, are commonly attributed to luminescence produced by native defect states in the material. , …”
Section: Resultsmentioning
confidence: 92%
“…The InGaN films on LT-GaN exhibit emissions corresponding to the near-band transitions (NBE) of GaN located at approximately 3.4 eV, as observed in Figure a . Additionally, a higher-intensity emission between 3.1 and 2.8 eV can be observed and attributed to InGaN NBE because of the shift toward a lower energy according to the indium composition . The band and shoulder observed at 2.62 and 2.26 eV, respectively, are commonly attributed to luminescence produced by native defect states in the material. , …”
Section: Resultsmentioning
confidence: 92%
“…It was also shown that formation of intermetalic Laves phases in titanium and ZrNb alloy is possible via Cr + ion implantation [17,18]. Irradiation with Cr + ions can also change magnetic properties of semiconductors like InGaN or CdTe [19,20] as well as minerals like rutile [21]. It was also shown that Ni + implantation followed by annealing leads to formation of magnetic nanoparticles e.g.…”
Section: Introductionmentioning
confidence: 99%